ELENA MARIA ŞORBAN – BOOK QUARTET: 1. THE HISTORY OF MUSIC AND US: CREATIVE PERMANENCIES, 2. THE OLD MUSIC. A CONCISE HISTORY, 3. CLASSICAL AND ROMANTIC MUSIC, 4. THE NEW MUSIC Eikon Publishing House, Cluj-Napoca, 2013 & 2014 - HOTORAN, Anamaria Mădălina (Studia Universitatis Babes-Bolyai Musica, 2014)
By the end of 2013 and the beginning of 2014, Elena Maria Şorban published a book tetralogy, a comprehensive compendium covering the entire music history, from the ancient music to the contemporary creations. Mrs. Şorban is Associate Professor Ph. D at the “Gheorghe Dima” Music Academy of Cluj-Napoca, where she teaches Music History and Gregorian Paleography. Her main fields of interest are Western Plainchant (with a doctoral dissertation on Plainchant in Medieval Transylvania), Modern and Contemporary Music and pedagogical applications of Music History for children. It is a pleasure and an honour to present her books, the more so as during my university years I had the privilege of attending Mrs. Şorban’s classes and of admiring the qualities of a complex and rigorous musicologist.